C-Glucopyranosyl-1, 2, 4-triazol-5-ones: synthesis and inhibition of glycogen phosphorylase. (24th June 2016) - Bokor, Éva; Széles, Zsolt; Docsa, Tibor; Gergely, Pál; Somsák, László
Highlights: Synthesis of 3- C -β-D-glucopyranosyl-1, 2, 4-triazol-5-ones. Enzyme assays against rabbit muscle glycogen phosphorylase. Low micromolar inhibition of the prototype of glycogen phosphorylases. Graphical abstract: Abstract: Various C -glucopyranosyl-1, 2, 4-triazolones were designed as potential inhibitors of glycogen phosphorylase. Syntheses of these compounds were performed with O -perbenzoylated glucose derivatives as precursors. High temperature ring closure of N 1 -carbamoyl- C -β-D-glucopyranosyl formamidrazone gave 3-β-D-glucopyranosyl-1, 2, 4-triazol-5-one. Reaction of N 1 -tosyl- C -β-D-glucopyranosyl formamidrazone with ClCOOEt furnished 3-β-D-glucopyranosyl-1-tosyl-1, 2, 4-triazol-5-one. In situ prepared β-D-glucopyranosylcarbonyl isocyanate was transformed by PhNHNHBoc into 3-β-D-glucopyranosyl-1-phenyl-1, 2, 4-triazol-5-one, while the analogous 1-(2-naphthyl) derivative was obtained from the unsubstituted triazolone by naphthalene-2-boronic acid in a Cu(II) catalyzed N -arylation. Test compounds were prepared by Zemplén deacylation. The new glucose derivatives had weak or no inhibition of rabbit muscle glycogen phosphorylase b: the best inhibitor was 3-β-D-glucopyranosyl-1-(2-naphthyl)-1, 2, 4-triazol-5-one (Ki  = 80 µM).